ANALISIS PENGARUH CURRENT RATIO, RETURN ON ASSETS, DEBT TO EQUITY RATIO, DAN TOTAL ASSET TURNOVER TERHADAP KEBIJAKAN DIVIDEN (PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2016) - Merly Rosetiyana, 14.05.52.0275; N. Masdjojo, Gregorius (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and to analyze the effect of Current ratio, Return on Assets, Debt to Equity Ratio, and Total Assets Turnover of manufacturing company on 2014-2016.This research uses purposive sampling method in sample selection, with sample criteria is a company listed in Indonesia Stock Exchange during 2014-2016. Based on these criteria, obtained a sample of 95 company during the three-year observation period. Method analyze data in research by using multiple linear regression analysis method. The results showed that the loan to Current Ratio had a no significant positive effect on the Dividen Payout Ratio, Return on Asset had positive significant effect on the Dividen Payout Ratio. While Current Ratio Return On Assets, Debt to Equity Ratio, Total Assets Turnover no effect on dividend on the Dividen Payout Ratio of 95 manufactur company. Debt to Equity Ratio had a negative no significant effect on the Dividen Payout ratio, Total Assets Tturnover had a positive no significant effect on the Dividen Payout Ratio. The Source of the Variable of the independent variable to the dividend policy is as big contribution as 19,6%. Keywords: Current Ratio (CR), Return On Assets (ROA), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Dividen Payout Ratio (DPR)